دور الثقافة التنظيمية في تفعيل إدارة الجودة الشاملة بمؤسسات التعليم العالي - عرابي محفوظ (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجاريةوعلوم التسيير, 2018)
المستخلص باللغة العربية:تَهدِف هذه الدراسة إلى التعرف على دور الثقافة التنظيمية في تفعيل إدارة الجودة الشاملة بمؤسسات التعليم العالي في الجزائر وفق منهج وصفي تحليلي. وتم الاعتماد على أداة تقييم الثقافة التنظيمية للباحثَيْن (Cameron & Quinn) في تشخيص واقع الثقافة التنظيمية بمؤسسات التعليم العالي في الجزائر، والتي تتضمن ستة أبعاد هي: القيادة التنظيمية، إدارة العاملين، التماسك التنظيمي، التركيز الاستراتيجي، معايير النجاح، والخصائص الهيمنة. في حين تم قياس إدارة الجودة الشاملة من خلال ستة أبعاد وهي: دعم الإدارة العليا، رضا المستفيد، التحسين المستمر، المشاركة الكاملة، ربط الجامعة بالمجتمع، والتغذية العكسية.تَكوَّن مجتمع الدراسة من أساتذة وطلبة كليات العلوم الاقتصادية والتجارية وعلوم التسيير بكل من جامعة البويرة، بومرداس، الجزائر 03، والبليدة 02. وتم اختيار عينة عشوائية طبقية ذات تخصيص نسبي بالنسبة للأساتذة، وعينة عشوائية عنقودية بالنسبة للطلبة. وزعت عليهم استبيانات، وتم استرداد -على التوالي- 250 و292 استبياناً صالحاً للتحليل الإحصائي.ولقد توصلت الدراسة إلى عدة نتائج أهمها:الثقافة الهرمية هي الثقافة الحالية المهيمنة بمؤسسات التعليم العالي في الجزائر.وجود درجة ممارسة متوسطة لإدارة الجودة الشاملة بأبعادها المتمثلة في: (دعم الإدارة العليا، رضا المستفيد، التحسين المستمر، المشاركة الكاملة، ربط الجامعة بالمجتمع، والتغذية العكسية) بمؤسسات التعليم العالي في الجزائر.وجود علاقة ارتباط موجبة بين الثقافة التنظيمية بأبعادها مجتمعة (القيادة التنظيمية، إدارة العاملين، التماسك التنظيمي، التركيز الاستراتيجي، معايير النجاح، والخصائص المهيمنة) وإدارة الجودة الشاملة بمؤسسات التعليم العالي في الجزائر.وجود أثر ذو دلالة إحصائية عند مستوى معنوية $(\alpha \le 0.05)$ للثقافة التنظيمية بأبعادها مجتمعة على إدارة الجودة الشاملة بمؤسسات التعليم العالي في الجزائر.وجود فروق ذات دلالة إحصائية عند مستوى معنوية $(\alpha \le 0.05)$ في استجابة الأساتذة للثقافة التنظيمية السائدة بمؤسسات التعليم العالي في الجزائر تُعزى لمتغير الخبرة المهنية، وهي لصالح الفئة أقل من خمس (05) سنوات.Abstract: The present study aimed to identify the role of organizational culture to activate the application of total quality management within institutions of high education in Algeria through a descriptive and analytical approach, the dimensions of organizational culture included six steps for diagnosing organizational culture recommended by (Cameron & Quinn) in their Organizational Culture Assessment Instrument (OCAI) represented by: organizational leadership; management of employees; organization glue; strategic emphases; criteria of success; dominant characteristics, total quality management was measured in six dimensions: high administration support; Continuous improvement, all participation; stakeholder satisfaction; relation between university and community; feedback. The study was carried out cover the population of teachers and Students in economic & business & administration faculty at the University of Bouira; Boumerdes; Algeria 03, Blida 02, a proportionate stratified random sample of teachers and a multi-stage random sample of students was chosen, on the whole number of 220 teachers forms and 282 students forms were valid for statistical analysis. The study has found a number of results, such as:  Hierarchy Culture is dominant culture actually at the institutions of high education in Algeria.  The degree of practicing total quality management in all its dimensions: high administration support; Continuous improvement, all participation; stakeholder satisfaction; relation between university and community; feedback was average at the institutions of high education in Algeria.  There was a positive correlation relationship between the organizational culture in all its dimensions (organizational leadership; management of employees; organization glue; strategic emphases; criteria of success; dominant characteristics) and total quality management at the institutions of high education in Algeria.  There was a significant statistical impact of the organizational culture in all its dimensions on total quality management at the institutions of high education in Algeria at level (α≤ 0.05). There were significant statistical differences in sample teachers to organizational culture at the institutions of high education in Algeria due to experience at level (α≤ 0.05) to those who have experience less than 05 years
دراسة حالة عينة من الجامعات الجزائرية
Keywords: الجودة الشاملة; الثقافة التنظيمية; مؤسسات التعليم العالي في الجزائر; القيادة التنظيمية; إدارة العاملين; التماسك التنظيمي; التركيز الاستراتيجي; معايير النجاح; الإدارة العليا; رضا المستفيد; التحسين المستمر; المشاركة الكاملة; ربط الجامعة بالمجتمع; التغذية العكسية